Effects of purification on the hydrogen production in biomass gasification process - Muhammad Bilal, Muslim; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Italian Association of Chemical Engineering - AIDIC, 2017)
Energy from renewable sources such as biomass are expected to complement the energy derived from fossil fuel resources due to its abundant reserves and relatively low price compared with other energy sources. These biomass wastes are used to produce hydrogen gas via gasification process. In order to study the gasification process, there have been substantial researches involving gasification using process simulation studies where the most commonly used is Aspen Plus software. The researcher basically often uses different types of gasifier in their studies where the most preferred in the literature are fluidized bed gasifier and downdraft fixed bed gasifier. The previous research did not focus on hydrogen gas purification produced from biomass gasification process. The objective of this research is to evaluate the performance of biomass gasification purification on the hydrogen production. The biomass used in this paper is oil palm frond since it is the most abundant waste produced compared to another oil palm wastes. Both of the fluidized bed gasifier and downdraft fixed bed gasifier models are developed in the Aspen Plus and the performance of the gasifier is determined by focusing on the total amount of hydrogen gas. Based on the gasification-purification simulation results obtained, the fluidized bed reactor produces approximately 7.95 % amount of hydrogen gas compare to only 6.75 % hydrogen gas for fixed bed reactor.